ANTESEDEN PROBABILITAS FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Triani Pujiastuti; Yuharningsih Yuharningsih (Jurnal Keuangan dan Perbankan, 2014)
Based on theory and previous research, some factors which influenced probability of corporate financialdistress were found. This research was done for testing the consistency of research result with different researchperiod that would strengthen the related empirical research finding. The purpose of this research was to test theimpact of profitability ratio (Return on Assets), working capital policy, capital structure, size, current ratioand firm age toward the probability of financial distress of manufacturing firms at Indonesian Stock Exchange.The method used in this research was purposive sampling, which was taking data with certain criteria.The criteria was that the companies or firms used were those which issued bond and were listed in IndonesianStock Exchange between 2007 until 2012 and had data completion needed in this research. The research resultsusing Logistic Regression were 1) test of profitability ratio, working capital policy ratio, capital structure, size,and firm age had significant influence to the probability of financial distress manufacturing firms in Indonesia,2) partially only profitability ratio that had negative significant influence to the probability of financialdistress manufacturing firms in Indonesia while working capital ratio, capital structure, size, and age firm didnot have significant influence to financial distress manufacturing firms in Indonesia. This research producedprediction model of financial distress.